Influence of Disclosure Corporate Social Responsibility Toward Sustainable Economic Development With Financial Performance as An Intervening Variable - Muhammad Faizul Mamduh; Ratno Agriyanto; dessy noor farida (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
Companies in carrying out their business have obligations to stakeholders in any form. CSR is one of the company's responsibilities for the activities carried out so far to the surrounding environment. In reality the CSR program has not been able to speak much in helping to improve the welfare of the community through sustainable development. This can be seen from the percentage of poverty in Indonesia that is still quite high. BPS noted that the highest poverty rate was in eastern Indonesia, namely the islands of Maluku and Papua with a percentage of 21.45%. This study aims to determine the effect of corporate social responsibility disclosure on sustainable economic development with financial performance as an intervening variable (an empirical study of mining companies listed on the 2016-2018 Syariah Securities List). The method used in this study is a quantitative method using the Warp PLS 4.0 application. The results of this study state that there is a significant influence and positive relationship between corporate social responsibility and sustainable economic development. There is a significant influence and positive relationship between corporate social responsibility and financial performance. And financial performance as an intervening variable significantly and positively influences between corporate social responsibility and sustainable economic development.